Membrane-associated Sulfur Oxidation by the Autotroph Thiobacillus thiooxidans - Adair, Frank W. (1966)
Adair, Frank W. (Rutgers, The State University, New Brunswick, N. J.). Membrane-associated sulfur oxidation by the autotroph Thiobacillus thiooxidans. J. Bacteriol. 92:899–904. 1966.—Washed cell wall-membrane fragments derived from sulfur-grown cells of the strictly autotrophic bacterium, Thiobacillus thiooxidans, oxidized elemental sulfur to sulfate without the addition of cofactors. The oxidation was optimal at pH 7.0 and was increased by the presence of wetting agents. Oxygen uptake was inhibited by cyanide, azide, and thiol-binding agents. Sulfite was also oxidized, and both the sulfur- and sulfite-oxidizing systems were heat-labile. Neither thiosulfate nor tetrathionate was oxidized by soluble or membrane preparations. The fragments fixed C(14)O(2) in the presence of ribose-5-phosphate, Mg(++), and adenosine triphosphate. Sulfur oxidation did not provide energy for C(14)O(2) fixation in this system.